PENGARUH PEMBERIAN KACANG MENTE SANGRAI TERHADAP PENURUNAN SKALA NYERI DESMINOREA PRIMER PADA REMAJA PUTRI DI SMA NEGERI 1 DELI TUA TAHUN 2025 - Purba, Tetty Junita; Siregar, G.F Gustina; Noni, Noni (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2025)
Primary dysmenorrhea is a frequent complaint of menstrual discomfort among adolescent females and can significantly disrupt their daily routines. The reliance on pharmacological analgesics, however, is often accompanied by unwanted side effects. Roasted cashew nuts are a natural source of magnesium, a mineral known for its function in reducing discomfort associated with uterine smooth muscle contractions.This research aimed to evaluate the influence of roasted cashew nut consumption on the reduction of dysmenorrhea pain intensity in adolescent girls. A quantitative method with a pre-experimental one-group pretest-posttest design was employed. The study population included students at SMA Negeri 1 Deli Tua who were identified as experiencing primary dysmenorrhea. Participants received roasted cashew nuts twice daily for two consecutive days during menstruation. Pain levels were recorded before and after the intervention using the Numeric Rating Scale (NRS). Findings indicated a reduction in dysmenorrhea severity following the intervention. Statistical analysis confirmed a significant correlation between roasted cashew nut intake and reduced menstrual pain (p < 0.05). Therefore, the study concludes that roasted cashew nuts are effective in minimizing the pain scale of primary dysmenorrhea and can serve as a natural, non-pharmacological alternative for menstrual pain management.